Antioxidant and Antiproliferative Potentials of Curcuma neilgherrensis Leaf Extracts, With Emphasis on Phytochemical Profiling and Apoptosis Induction in Colorectal Carcinoma HCT116 Cells by the Chloroform Extract - Soumya Tumbath; T. Lakshmipriya; P. R. Jayasree; P. R. Manish Kumar (Scientifica)
Zingiberaceae family of plants are ethnomedicinally well known. One of the less-studied endemic species from this family, Curcuma neilgherrensis, and its leaves have been used as a folklore medicine by tribes of Western Ghats of India since ancient times. The aim of the study is to investigate in vitro antioxidant and antiproliferative potentials of organic solvent extracts prepared from C. neilgherrensis leaves as well as phytochemical profiling of the selected extract capable of apoptotic induction in cancer cells. In vitro antioxidant activity was evaluated by the estimation of total phenolics and flavanoid contents, DPPH, ABTS radical scavenging, and lipid peroxidation inhibition assays. Cytotoxic/antiproliferative potential was assessed employing human cancer cell lines (K562, HCT116, MDA-MB-231, and HL60) and normal lymphocyte cultures by MTT and trypan blue dye exclusion assays. Fluorescence microscopy, flow cytometry, DNA fragmentation, and caspase activity assays were utilized to study apoptosis induction by the extract in HCT116 cells. HR-ESI-MS/MS was used to identify chemical constituents present in the extract. C. neilgherrensis leaves extracts were found to contain varying amounts of total phenolics and flavanoid contents as well as antioxidant activity, with the methanolic extract (CNLM) displaying maximal activity. Higher antiproliferative potential was shown by the chloroform extract (CNLC) for a 48 h treatment period, against colorectal carcinoma HCT116 cells (IC50-8.3 ± 0.8 μg/mL). CNLC treatment caused cytomorphological alternations, phosphatidylserine externalization, reduction in mitochondrial membrane potential, increase in intracellular ROS, sub-G1 phase cell population, and DNA fragmentation, as well as caspase 3 and 9 activities, confirming apoptosis induction in HCT116 cells. Phytochemical profiling of the CNLC extract by HR-ESI-MS/MS enabled identification of bioactive compounds, previously reported with anticancer potential such as rutin, tamarixetin, embelin, ginkgolide B, traumatic acid, and rosmarinic acid. To our knowledge, this is the first report demonstrating in vitro antioxidant and antiproliferative potentials of C. neilgherrensis leaf extracts. The results presented reveal that C. neilgherrensis leaves are indeed a potent bioresource for chemotherapeutic candidate drugs for future use.